Numerical simulation analysis of structural strength of portable skid for storage tank with 50.000 liter capacity - Muslimin Al Masta (Jurnal POLIMESIN, 2023)
AbstrackA storage tank is a container used to store fluids such as fuel, water, and chemical. Skid construction is implemented to make the tank smoothly transported while operated, such as in the mining field. Skids were assembled on the storage tank's base to sit on the ground. This study aims to design and analyze a portable skid storage tank to resist the load of 50,000 liters (392 kN) of fuel and 45 kN of mass of construction itself statically. The skid's main components are a wear plate, pad eye, and seamless pipes of schedule 40 for support, central, and base. All structure's material is 250 MPa yield strength of ASTM 36 low carbon steel. Manual calculations and simulation analysis were implemented to review the skid structure's maximum stress and safety factor. The examination included pipe support, central pipe, and pad eye. Based on the result, the highest stress of 157.88 MPa by ANSYS and 148.07 MPa by manual calculation. Therefore, the construction is safely based on the Tresca and Von Mises criteria.